Identifying the parameters of the Malay classical architecture - Raja Abdul Kadir, Tengku Anis Qarihah; Jahn Kassim, Puteri Shireen; Abdul Latip, Nurul Syala; Md. Sharif, Harlina (Malaysian Institute Of Planners, 2020)
As modernization and urbanization grow, there has been a rising interest in townships with historical elements in their urban landscape. The identification and classification of Malay architectural language are crucial to architects seeking to instill history and culture into the new design. The paper traced the characterizations of classicality in Malay architecture through a thorough study of palaces and aristocrat buildings in Malaysia. Morphological analysis of 50 case studies was mapped but only six palaces from different sites and eras were marked as samples in this paper. The focus of the study not only on their origins, typology, history, and stylistic characters but also on the proportions and elemental attributes of the frontal façade. These case studies were selected as sentinels or samples of successive evolutionary phases in classical Malay architecture which had a huge gap and carried different historical evolutions. It was argued that while the earlier palaces reflected all Malay style attributes, the later expression reflected the cultural pressure of globalization via colonialism diffused from colonial institutions. The study extracted the five parameters of the Malay classical architecture, whereby it was found that even under such pressure, certain features were still maintained to root the identity of the Malays and later developed as new city urbanscape.